EFEKTIFITAS PEMBERIAN PERMEN JAHE TERHADAP MUAL MUNTAH PADA IBU HAMIL DI RUMAH SAKIT UMUM DAERAH RAJA AHMAD TABIB TANJUNGPINANG - Elena, Elena; Sihombing, Sarmauli Franchisca; Fahnawal, T. Marzila (Universitas Batam, 2021)
Nausea and vomiting that occur in pregnancy are caused by an increase in the hormones estrogen and progesterone produced by HCG in serum from the placenta. In emesis gravidarum, if not treated immediately, it will result in weight loss due to inadequate maternal nutritional intake resulting in increased incidence of fetal growth disorders, low birth weight, and congenital defects in the fetus. The purpose of the study was to determine the effectiveness of giving ginger candy to nausea and vomiting in pregnant women. The research method is Quasy experimental with